Thinking Process Analysis Reflective Student in Solve Problem Non-routine on Probability Material - Asmaun, Asmaun; Baharuddin, Baharuddin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The problem faced by students in school is the lack of a thinking process that is able to link existing knowledge with problems that are rarely encountered before. The reflective thinking process is one of the important aspects in solving non-routine problems and can be viewed from students' mathematical abilities. Therefore, this study aims to describe the reflective thinking process of class XI IPA 1 students of SMAN 10 Makassar with high initial mathematical abilities in solving non-routine mathematical problems. This study is a descriptive study using a qualitative approach. The results obtained in this study are that students with three subjects with high initial mathematical abilities have a reflective thinking process in four problem-solving steps (polya) as follows (1) understanding the problem: (a) elaborative-creative thinking, (b) clarification-critical thinking, (c) critical-assessment thinking and (d) creative-laboratory thinking, all indicators are met by all subjects. (2) developing strategies: (a) inferential-critical thinking, (b) elaborative-creative thinking and (c) fluent-creative thinking, all indicators are met by all subjects except for the fluency indicator, there is one subject that does not meet it. (3) implementation strategy: (a) inferential-critical thinking is fulfilled by the subject, (b) flexible-creative thinking, only two subjects fulfill the indicators and (d) originality-creative thinking can only be fulfilled by one subject. (4) looking back: (a) elaborative-creative thinking and (b) critical thinking strategy, all indicators are fulfilled by the subject, but only one student checks the answer.